Socioscientific Issues-Based Learning as an Effort to Train High Order Thinking Skills in Junior High School Students - Riva Ismawati; Utami Dian Pertiwi (Universitas Tidar, 2019)
The development of Science and Technology has a positive and negative impact. The negative impact caused by the development of science and technology shows that education is faced with the challenge of producing graduates who have the ability to solve problems. Meanwhile, on the other hand it is known that the scientific literacy skills of students in Indonesia are still low. The socioscientific issue is an important element that needs to be presented in science and technology learning activities. The purpose of the article is to describe the application of socioscientific issues-based learning as an effort to train high order thinking skills in junior high school students. This article is a literature study where related articles are reviewed and the information obtained is compiled into a writing.